Answer:
29.) 6x² + 12x + 42
30.) 4x - 4x²
30.) -x³ - 5x²
31.)
32.) -3x³ + 6x² - 36x
Explanation:
29. 6 ( x² + 2x + 7 )
* distribute the 6 to what's inside of the parenthesis *
6 * x² = 6x²
6 * 2x = 12x
6 * 7 = 42
6x² + 12x + 42
30. 4x ( 1 - x )
* distribute the 4x to what's inside of the parenthesis *
4x * 1 = 4x
4x * -x = -4x²
4x - 4x²
For some reason there is two number 30's
-x² ( x + 5 )
* distribute the -x² to what's inside of the parenthesis *
-x² * x = -x³
-x² * 5 = -5x²
-x³ - 5x²
31.) 3x² ( 4x³ - 5x + 10 )
* distribute the 3x² to what's inside of the parenthesis *
![3x^2*4x^3=12x^5\\3x^2*-5x=-15x^3\\3x^2*10=30x^2\\12x^5-15x^3+30x^2](https://img.qammunity.org/2022/formulas/mathematics/high-school/b11co1nskt8t3ghqg2ig6t130gx02sqoia.png)
32.) 3x ( -x² +2x - 12 )
* distribute the 3x to what's inside of the parenthesis *
3x * -x² = -3x³
3x * 2x = 6x²
3x * -12 = -36x
-3x³ + 6x² - 36x
Note: When multiplying variables with constants and exponents you add the exponents and multiply the constants
Ex. 3x² * 4x²
Multiply the constants ( 3 and 4 )
3 * 4 = 12
Add the exponents
![^2^+^2^=^4](https://img.qammunity.org/2022/formulas/mathematics/high-school/akxpsarq9xmwos8n5k2fegol7ouvduc6aj.png)
![3x^2*4x^2=12x^4](https://img.qammunity.org/2022/formulas/mathematics/high-school/ypmmosihjvw6llvqgq2yar1rc52uk79wh2.png)